Nutrient Profiles and Glycemic Potentials of Noodles from Beneng Taro (Xanthosoma undipes K. Koch) - Pratama, Wahyu; Sulaeman, Ahmad; Nasution, Zuraidah (Jurnal Teknologi dan Industri Pangan, 2026)
This study explores the development of functional noodles made from modified beneng taro (Xanthosoma undipes K. Koch) flour, modified cassava flour (mocaf), and soy protein isolate (SPI) aiming to promote food diversification and offer a nutritious alternative for individuals with metabolic disorders. The research employed a completely randomized design (CRD) with three formulations as follows: F1 (50:40:10), F2 (50:35:15), and F3 (50:30:20) of modified beneng taro flour, mocaf flour, and SPI. The noodles was analyzed for dietary fiber, proximate composition, sensory evaluation, starch, and glycemic index. The modified beneng taro flour was produced through lactic acid fermentation using a commercially available mixed-culture starter (Bimo CF), followed by drying and milling. Dietary fiber analysis showed that formula F1 with 50% modified beneng taro flour, 40% mocaf flour, and 10% SPI had the highest fiber content (12.3 g/100 g). The sensory evaluation indicated that the formula F2 with 50% modified beneng taro flour, 35% mocaf flour, and 15% SPI was preferred for its color, texture, taste, and overall acceptance. Based on sensory preference, further nutritional, starch, and glycemic analyses were conducted on formula F2. The selected formula had a nutritional profile as follows: 13.2 g/100 g moisture, 2.6 g/100 g ash, 15.1 g/100 g protein, 1.2 g/100 g fat, 67.7 g/100 g carbohydrates, 64.1 g/100 g starch, 58.4 g/100 g in vitro starch digestibility, and 5.8 g/100 g resistant starch. The glycemic index was 43.6 (low) with a moderate glycemic load of 16.9. The postprandial glucose response showed better control than with pure glucose. The integration of modified beneng taro flour, mocaf flour, and SPI in formula F2 produced a nutritionally balanced noodle with good sensory qualities, high fiber and protein content, and a low glycemic index. This research highlights the potential of local ingredients for food diversification and the creation of healthier dietary options.